1997
DOI: 10.1091/mbc.8.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for physical and functional interactions among two Saccharomyces cerevisiae SH3 domain proteins, an adenylyl cyclase-associated protein and the actin cytoskeleton.

Abstract: In a variety of organisms, a number of proteins associated with the cortical actin cytoskeleton contain SH3 domains, suggesting that these domains may provide the physical basis for functional interactions among structural and regulatory proteins in the actin cytoskeleton. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
219
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(228 citation statements)
references
References 78 publications
9
219
0
Order By: Relevance
“…On the basis of the intracellular localization of DBN-1 and on a tentative functional comparison with its relatives, DBN-1 could furthermore modulate the plasticity and function of postsynaptic sites of neuromuscular junctions, analogous to mAbp1 and drebrin, which are known as essential players in both neurological [43][44][45]28 and immunological 30,29 synapses. In addition, DBN-1 may be involved in vesicle transport, similar to yeast and mammalian Abp1 homologues, which are well-described key regulators of receptor-mediated endocytosis, vesicle trafficking and endocytic structure disassembly [46][47][48][49]32 .…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the intracellular localization of DBN-1 and on a tentative functional comparison with its relatives, DBN-1 could furthermore modulate the plasticity and function of postsynaptic sites of neuromuscular junctions, analogous to mAbp1 and drebrin, which are known as essential players in both neurological [43][44][45]28 and immunological 30,29 synapses. In addition, DBN-1 may be involved in vesicle transport, similar to yeast and mammalian Abp1 homologues, which are well-described key regulators of receptor-mediated endocytosis, vesicle trafficking and endocytic structure disassembly [46][47][48][49]32 .…”
Section: Discussionmentioning
confidence: 99%
“…The null mutation of the yeast homologue of Abp1, Abp1p, resulted in defects similar to those seen in Rvs167/amphiphysin mutation, including sporulation and reduced viability under certain suboptimal growth conditions. Double mutations in ABP1 and RVS167/amphiphysin genes or one of the genes encoding other cytoskeletal components were genetic lethal (47). In mammalian cells, Abp1 has been shown to be essential for Tf internalization (33,40) and synaptic vesicle recycling (39).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that Abp1 was required for efficient BCR-mediated Ag internalization, further demonstrating an essential role for Abp1 in endocytosis. Previous studies have shown that Abp1 interacts directly with proteins of the endocytic machinery, including rvs167/amphiphysin in yeast (47) and dynamin in mammalian cells (33). Both amphiphysin and dynamin are important for the membrane fission step of endocytosis (38,48).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclaseassociated protein (CAP) also rapidly associates with SIinduced punctate actin foci. 29 In yeast (S. cerevisiae), CAP/ Srv2p localises to actin patches and is required for the formation of F-actin aggregates 57 and is found in the actin 'bodies' in stressed, quiescent yeast. 58 As CAP/ Srv2p binds to adenylate cyclase and facilitates initiation of cAMP signalling during PCD initiation in yeast, 59 it may mediate foci formation and may, perhaps, link actin reorganisation to PCDsignalling networks in plant cells too.…”
Section: How Is Regulation Of the Cytoskeleton To Mediate Pcd Achieved?mentioning
confidence: 99%